Factors of change effect attitudes and behaviors among staff at Bank Rakyat Jalan Hang Tuah Malacca / Norasiqin Razak - Razak, Norasiqin (Faculty of Business and Management, 2013)
Attitudes and behaviors requires in change that occur in the organization. It because motivated of employees to maintain their position and membership in a certain organization. In addition attitudes and behaviors is the important management to accept change for successful in organization change. Hence, the main objective of this research is to identify factor of change effect attitudes and behaviors among staff at Bank Rakyat Jalan Hang Tuah Malacca. Besides, researcher also identifies the main factor which effect attitudes and behaviors. The factors are technology change, culture change and environment change. Researcher used questionnaire as a main instrumental in data collection method. Next, data that been collected will be analyzed through using The Statistical Package for Social Science (SPSS) software version 18.0. In general, the results of this research showed that technology change is the most influence rather than culture and environment change toward attitudes and behaviors among staff at Bank Rakyat Jalan Hang Tuah Malacca.